Heat propagation in a material due to dry sliding friction - Ang, Emily Li Ting (2015)
The main objective of this project is to predict the surface temperature of a moving solid in which the boundaries except the sliding contact surface are insulated. In addition, the influence of various parameters on the thermal contact resistance as well as the heat flux in both stationary and moving solid are also studied. The predictions of the surface temperature are carried out theoretically by modelling the rough-rough surface based on Cartesian coordinates. To avoid complexity, the rough surface defects are assumed to have numerous square periodic asperities. In addition, the two contacting solids must be of a similar thermo-physical properties as well as surface geometry. Correlation for the sliding contact thermal resistance has been determined by P. Chantrenne and M. Raynaud. The simulation of heat transfer between sliding contacts is done computationally by using MATLAB, the processes via numerical solution of the governing equations. Discretization of the governing heat equation and boundary condition are done using the finite difference method.